La calidad de los programas de trabajo con familias y resultados en desarrollo infantil: El caso de Cuna Más en Perú - María Caridad Araujo; Marta Dormal; Marta Rubio-Codina (Inter-American Development Bank (IDB), 2019)
– This paper analyzes the association between quality of parenting programs and child development outcomes . It focuses on parenting programs delivered through home visits (i.e., home visiting programs) in which a par aprofessional works with the caregiver to improve parental practices, skills and knowledge of child develop ment , wi th an application to the Peruvian national program Programa Nacional Cuna Má s. Home visiting quality is measured through the Home Visit Rating Scale, version A+2 (HOVRS - A+2), and child development outcomes through the Ages and Stages Questionnaires (ASQ - 3) and the Bayley Scales of Infant and Toddler Development (Bayley - III). The empirical analysis used is descriptive in nature. Results show that home visiting quality scores are significantly associated with our measures of child development, but thi s association is not consistent across all measures
Keywords: I12; J24; O15; 330; home visiting; quality; child development; HOVRS-A+2; ASQ-3; Bayley-III